KESADARAN HUKUM SIVITAS AKADEMIKA DALAM BERLALU LINTAS DI LINGKUNGAN FAKULTAS HUKUM UNIVERSITAS RIAU - Simanjuntak, Dody Saputra; ', Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
This study aims to assess the condition of legal awareness of academicians in road traffic, the factors that influence the legal awareness of academicians in traffic as well as the efforts made to improve the legal awareness of academicians in traffic. This research was conducted in the Faculty of Law of University of Riau. This type of research that will be used is a sociological law research, because in this study the authors directly conduct research on location or places studied in order to give a complete and clear picture of the problem examined. While the sample population is whole party with regard to the issues examined in this study, the data source used, primary, secondary and tertiary, data collection techniques in this study by observation, interview, questionnaire and literature study.From the research, there are three basic problems that can be inferred. First, the level of legal awareness of academicians in traffic in Faculty of Law University of Riau still low, based on the knowledge, understanding, attitudes, and behavior of law academicians. Second, the factors that influence the legal awareness of academicians in traffic, namely (i) the absence of regulation or specific rules are made, (ii) the action is not firm, (iii) the lack of infrastructure / facilities such as signs or traffic signs, (iv) the common misperception that influenced academicians of knowledge and understanding of academicians. Third, efforts are being made improve the legal awareness of academicians in traffic, namely (i) need to be made regulation or specific rules, (ii) the need to provide guidance to the security officer and coordinate with police to enforce the law, (iii) make signs or traffic signs and parking areas, (iv) carry out the direction and guidance to the academic community.Keywords: Legal awareness ? academicians